FORMS OF ORGANIZATION OF INDEPENDENT EDUCATIONAL ACTIVITY OF STUDENTS OF HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2009)
Forms of organization of students' self-directed learning activities in higher pedagogical educational establishments are defined and theoretically backgrounded.